Supraceliac aortic cross-clamping to control bleeding from the celiac axis during pancreatic surgery: a case report - Yuki Takano; Shuichi Fujioka; Hironori Shozaki; Naoki Toya; Toru Ikegami (Surgical Case Reports)
Abstract Background Intraoperative bleeding from the celiac axis (CA) can occur during pancreatic surgery, and appropriate management is essential to avoid critical complications. Here, we have reported a case that was managed with supraceliac aortic cross-clamping (SAC) for arterial bleeding from the CA during pancreatic surgery. Case presentation A 70-year-old man was diagnosed with pancreatic cancer located in the pancreatic head and body. Preoperative computed tomography showed a stricture at the root of the CA, which may have been caused by a median arcuate ligament. Pancreaticoduodenectomy with division of the median arcuate ligament was scheduled. Uncontrollable bleeding from the root of the CA was observed during surgery. The bleeding was controlled by performing SAC, and a defect in the CA was confirmed. Arterial wall repair was successfully performed under temporal blood control using SAC. The aortic clamp time was 2 min and 51 s, and the intraoperative blood loss was 480 ml. Conclusions Although SAC is primarily a procedure for ruptured abdominal aortic aneurysm, it can be useful for the management of CA injuries during pancreatic surgery.